2007
DOI: 10.1590/s0102-261x2007000600006
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric 2-Day waves observed simultaneously in the equatorial and low latitudes regions of Brazil

Abstract: Simultaneous observations of the atmospheric neutral winds in the mesosphere and lower thermosphere (MLT) by meteor radar have been carried out at São João do Cariri (7.4 • S, 36.5 • W) and Cachoeira Paulista (22.7 • S, 45.0 • W). From the wind variability we investigate the atmospheric planetary-scale quasi-two-day waves, which were present at both the sites during the winter of 2004 and summer of 2004/2005. The amplitude of the meridional component was larger than that of the zonal component, reaching a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Also from the MF radar over Tirunelveli, Gurubaran et al (2001) found quasi 2-day waves dominated by meridional winds occurring during December to January months. Lima et al (2004) found that the quasi 2-day waves are dominated by meridional winds at Cachoeira Paulista occurring from December to February, while at Cariri, Lima et al (2007) found that the waves occur in December to February with the same characteristics as those observed at Cachoeira Paulista, but also in June to July. From meteor radar wind measurement over Ascension Island, Pancheva et al (2004) found the overall wind characteristics to be in agreement with those of other equatorial longitudes, and the zonal wind was dominated by 3-to 7-day waves while the meridional wind component by quasi 2-day waves around southern summer months.…”
Section: Introductionmentioning
confidence: 79%
“…Also from the MF radar over Tirunelveli, Gurubaran et al (2001) found quasi 2-day waves dominated by meridional winds occurring during December to January months. Lima et al (2004) found that the quasi 2-day waves are dominated by meridional winds at Cachoeira Paulista occurring from December to February, while at Cariri, Lima et al (2007) found that the waves occur in December to February with the same characteristics as those observed at Cachoeira Paulista, but also in June to July. From meteor radar wind measurement over Ascension Island, Pancheva et al (2004) found the overall wind characteristics to be in agreement with those of other equatorial longitudes, and the zonal wind was dominated by 3-to 7-day waves while the meridional wind component by quasi 2-day waves around southern summer months.…”
Section: Introductionmentioning
confidence: 79%
“…In the low latitudes with the meteor radar wind measurements, quasi-2-day planetary waves in the meridional component (Lima et al, 2004) and quasi-2-day waves in the meridional component accompanied by 3-7-day waves in the zonal component (Pancheva et al, 2004) were also reported. In the middle-to-low latitudes from the simultaneous observations of two meteor radar atmospheric neutral winds, a westward-propagating quasi-2-day planetary wave was observed (Lima et al, 2007). With temperature data from TIMED-SABER (Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics; Sounding of the Atmosphere using Broadband Emission Radiometry), Pancheva et al (2009) detected planetary-scale waves from the stratosphere to the lower thermosphere during the Arctic winter of 2003-2004.…”
Section: Introductionmentioning
confidence: 99%